INSTITUTIONAL RACISM IN ANGIE THOMAS’ THE HATE U GIVE - FANANI, M. Pd., Dr. ABU; YANTI, S. S., NISA RITMA (Faculty of Letters, Dr. Soetomo University, 2020)
Yanti, N. R. and Fanani, Abu (2020). Institutional Racism in Angie Thomas’ The Hate U Give. Keywords: racism, institutional racism, African American literary criticism. This article tries to analyze a novel written by Angie Thomas entitled The Hate U Give and focuses on the main character named Starr Carter. The purpose of this article is to know racism that occurs in the novel and the way Starr has to deal with it. The method used in this study is qualitative research or library research, it means the data are concerned with texts, written words, phrases or symbols. Primary data source of this research is taken from the novel while secondary data sources are taken from articles, journals, websites, and books that relate with this analysis. The collected data are analyzed by applying institutional racism theory in African American literary criticism. As the result of the analysis it is found that there are three parts of institutional racism portrayed in this novel, those are ignorance toward Black Panthers’ Ten-Point Program, the shooting in license checking, and physical punishment in police patrol.